DESAIN DIDAKTIS MATERI PENGENALAN OPERASI ALJABAR UNTUK SISWA SEKOLAH MENENGAH PERTAMA (SMP) - Ade Riastuti, - (2023)
This study aims to describe the didactic design of materials for introducing algebraic operations in a comprehensive manner using modelsproblem based learning for junior high school (SMP) students, to achieve this goal, this research is based on qualitative research withdidactical design research (DDR). Participants in this study were 25 class VIII students to identifylearning obstacle in the introduction of algebraic operations material, while in 33 class VII students as subjects to implement the didactic design of material introduction to algebraic operations using the methodproblem based learning. Data collection was carried out through data triangulation, namely written tests, interviews, and documentation studies. Based on the results of the study showed that students experienced severallearning obstacle that isontogenic obscale caused by the incompatibility of the problems given with the knowledge of the prerequisite material possessed by students,epistemology obstacle there is a limited knowledge of students in interpreting the meaning of variables in algebraic operations, anddidactical obstcle caused by the learning experience of students working on questions about algebraic operations and sourced from the presentation of teacher material and learning resources such as textbooks. Based on research resultslearning obstacle identified, the didactic design of material for introducing algebraic operations was prepared by using a modelproblem based learning which can be used in the learning process.